Analisis Kebutuhan Tenaga Kerja Lulusan Sekolah Menengah Kejuruan Teknik Kendaraan Ringan di Kabupaten Karawang Tahun 2020-2024 - Dea Pratami; Aceng Muhtaram Mirfani; Taufani Chusnul Kurniatun; Diding Nurdin (Universitas Pendidikan Indonesia, 2021)
This research aims to determine and analyze the labor needs of Light Vehicle Engineering Vocational High School graduates at Karawang Regency in 2020-2024. The method used in this research is qualitative method. This research was conducted using a manpower planning approach, which is used based on commonly used theories and compared with those used in the industry that is the benchmark. Participants in this research were all State Vocational Schools in Karawang Regency which had light vehicle engineering expertise programs. The results of the research found four main points, namely the first, the automotive industry in Karawang Regency experienced a significant growth acceleration in the last five years in the 2015-2019 period. Second, to encourage the acceleration of the automotive industry in Karawang Regency which is growing in the future. Based on the results of calculations using the manpower planning approach in the next five years, it takes at least 164 technicians in the field of plant productivity accompanied by competency specifications of expertise that require mastering the field of industrial automation. Third, the need for technicians in the field of plant productivity in 2024, which is as many as 164 technicians, can be met through only 6 of Vocational High School. Fourth, the need for labor in the middle quality category is oversupply, one of the factors for the oversupply is because the absorption of graduates does not focus on industry in Karawang Regency.